Pragmatic Institution of Baiturrahman Mosque for Surrounding Street Vendors Through Islam Architecture - Deni Deni; Aris Munandar; Abdul Razak Nawaf; Nayeem Asif (Universitas Sarjanawiyata Tamansiswa, 2025)
The Baiturrahman Mosque is a central landmark in Banda Aceh, surrounded by 133 street vendors engaged in economic activities to earn a living. Less than 10% of these street vendors earn just enough to survive. Based on reference research, the concept of Islam architecture, which incorporates self-help mosques, has been proposed by the majority as a community empowerment mosque. While it offers a more realistic opportunity for implementation, it has limited scope for significant change. This study seeks to tap the Baiturrahman Grand Mosque, managed by the local provincial government, as a broader approach to change, enabling a mosque to participate in improving the quality of life of the surrounding community. This exploratory qualitative study explores information on the mosque's institutional programs and the characteristics of street vendors. This information will be analyzed using the architectural dialectic phenomenon method, using the eight principles of Islam architecture as a conceptual framework. The results are compared with the essence of the policy level. The analysis reveals that the mosque's institutional programs are therapeutic at a non-participatory level, not yet significant in the context of social worship practiced by the surrounding street vendors.